Investigation of hydrogen usage on combustion characteristics and emissions of a spark ignition engine - Karagoz, Yasin; Balci, Ozgan; Koten, Hasan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In this study, initially, a single cylinder, naturally aspirated, spark ignition engine was loaded with AC engine dynamometer and a spark plug type engine transducer was used to obtain in-cylinder pressure. The test engine was operated with gasoline fuel at full load and different engine speeds (3100, 3200, 3300, 3400 and 3450 rpm). Secondly, using obtained engine performance, emission values and in-cylinder pressure, a one dimensional engine model was built and validated by an engine performance and emission analysis software (AVL-Boost). After the validation of single dimensional theoretical engine model, a comparison was made between the emission, performance and combustion (in-cylinder pressure, rate of heat release) values of operations with pure hydrogen fuel and such values of the operations with unleaded gasoline. The emissions of CO and total hydrocarbons (THC) were negligible with using hydrogen as fuel in SI engine. A dramatic increase in NOx emissions was obtained with using hydrogen as fuel. However, by using hydrogen in lean conditions, NOx emissions were taken under control by means of wide flammability limits of hydrogen. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; NOx; THC; CO; Heat release rate; LEAN BURN PERFORMANCE; GASOLINE-ENGINE; SI ENGINE; Chemistry; Electrochemistry; Energy & Fuels